(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
The unsteady free convection flow of an incompressible viscous fluid past an exponentially accelerated vertical plate is analyzed by taking into an account the heat due to viscous dissipation under the influence of a uniform transverse magnetic field. The problem is governed by coupled non-linear partial differential equations. Dimensionless equations of the problem have been solved numerically by the implicit finite difference method of Crank – Nicolson’s type. The effect of magnetic parameter M, Grashof number Gr, Eckert number E, time and an acceleration parameter a on velocity and temperature fields are investigated through graphs. Skin friction coefficient is derived, discussed numerically and presented through a table. DOI: 10.3329/jname.v7i2.4370